Holistic Integration: Syariah Finance Principles in Islamic Education Management - Jinan, Muhammad Riyadlul; Syapiuddin, Muhammad; Nasri, Ulyan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Islamic education management requires a holistic approach that considers Islamic values in every aspect, including financial management. This article discusses the integration of Shariah finance principles into Islamic education management to achieve financial sustainability and promote Islamic moral values. The main principles of Shariah finance, including transparency, justice, risk-sharing, and prohibition of interest, are the primary focus of this research. The research methodology adopts a qualitative approach through literature review and interviews with experts in Shariah finance and Islamic education. Data analysis techniques involve categorizing information and synthesizing findings relevant to the integration of Shariah finance principles into Islamic education management. The results indicate that integrating Shariah finance principles into Islamic education management can enhance efficiency, fairness, and sustainability of educational institutions. The implications of this research emphasize the importance of training and education for Islamic education practitioners to apply Shariah finance principles in their management practices. The holistic integration of Shariah finance principles into Islamic education management not only creates financially sustainable educational institutions but also strengthens the religious and cultural identity of Muslim communities. This supports the vision of Islamic education encompassing spiritual, moral, and academic aspects.